Nitrato encapsulado na suplementação para novilhos de corte em pastejo - Berti, Guilherme Felipe (2020)
The present work evaluated the effects of the partial replacement of soybean meal with encapsulated nitrate in suplemented grazing beef cattle diets. The experimental design was a cross-over, conducted in two consecutive periods of 21 days each. Eight crossbred steers (average body of 345 kg), castrated, fitted with ruminal cannula were distributed in two treatments: Control - multiple supplement based on soybean meal, without nitrate; and NE - supplement with encapsulated nitrate (5% on the concentrate dry matter), replacing soybean meal. Each animal were daily supplemented with 1.0% of his body weight. The data were analyzed using mixed models, using the MIXED procedure of the SAS program and comparisons between treatments were made using the F test, at the level of 5% probability. The total dry matter intake (DMI) was not affected (P = 0.459), as well as the forage DMI (P = 0.906). However, a decreae of the concentrate DMI rate (% body weight) was observed (from 0.92% to 0.88%) (P = 0.024). Control and EN animals showed higher concentrate intake during three hours after feed, however EN had lower and slower consumption throughout the day. The use of EN did not change the digestibility of the dry matter (P = 0.090), as well as the digestibility of the crude protein (P = 0.160), neutral detergent fiber (P = 0.122) and non-fibrous carbohydrate (P = 0.872), but decreased the ether extract digestibility from 68.81% to 61.21% (P <0.05). The EN decreased butyrate (P <0.01) and valerate rates (P <0.0095) 9 hours after feeding. There was no effect of EN on propionate (P> 0.1215) and total AGCC rates (P> 0.8620), whereas EN increased the total acetate rates 3, 6 and 12 hours after supplementation (P <0.0018). There was no effect of EN on the ruminal NH3 concentration (P> 0.5845). In summary, EN provides lower palatability to concentrate diets, maybe increasing the time spent in the trough throughout a day, but did not decreases the dry matter intake of suplemented grazing cattles.